Effect of SiHuangQingXinWan on Klebsiella pneumoniae-induced pneumonia: mechanistic insights - Liu, Haihui; Sun, Xiaoluo; Tao, Sian; Liu, Shu; Wang, Xin; Chen, Qiuping; Wu, Wenjun; Xi, Chongcheng; Li, Baixue; Feng, Quansheng; Liu, Jibin (Frontiers in Pharmacology, 2024)
Introduction Due to the high mortality rate and increasing severity of antibiotic resistance, there is a growing interest in new treatments for Klebsiella pneumoniae (KP)-induced pneumonia. Research has shown that the single herbs of SiHuangQingXinWan (SHQXW) are effective in treating pneumonia caused by KP. The PI3K/AKT signaling pathway has garnered attention for its potential role in the management of bacterial infections. This study aimed to evaluate the anti-pneumonia effect of SHQXW and to investigate its mechanism of action. Materials and Methods The potential plant metabolites and molecular targets of SHQXW in the context of pneumonia were determined through ultra-high performance liquid chromatography-tandem mass-spectrometry (UHPLC-MS/MS) and bioinformatics analysis. The therapeutic effect of SHQXW was evaluated in a KP-induced pneumonia murine model with imipenem/cilastatin as a positive control. Transcriptomics and non-targeted metabolomics were carried out to unveil potential mechanisms and targets for anti-pneumonia effects. Additionally, an in-depth exploration on the PI3K/AKT signaling pathway was conducted in this study. Results A total of 24 potential plant metabolites and 285 SHQXW-pneumonia-related targets selected by Homo sapiens were identified in this study. The tested doses of SHQXW significantly reduced mortality, improved body weight, decreased the lung index, reduced the bacterial load, and alleviated lung pathological damage in the KP-induced pneumonia murine model (p < 0.05). Notably, 1.3 g/kg/day of SHQXW provided the most effective protective outcome. Furthermore, SHQXW demonstrated the ability to suppress the production of inflammatory factors such as IL-1α, IL-1β, IL-3, IL-6, IL-12p70, G-CSF, GM-CSF, MCP-1, KC, and TNF-α. Analysis of transcriptomic and metabolomic data revealed that SHQXW could modulate inflammation-related signaling pathways (TNF, HIF-1, NF-κB, and PI3K/AKT) and metabolites to regulate pulmonary inflammation. Additional experiments using RT-qPCR and western blotting indicated that SHQXW may exert anti-inflammatory effects by activating the PI3K/AKT pathway. Discussion The findings indicate that SHQXW effectively reduces inflammation in mice with KP-induced pneumonia by modulating inflammatory signaling pathways and metabolites, rather than by directly inhibiting the growth of KP. This study introduces a novel treatment approach for KP-induced pneumonia and presents a new outlook on drug development.